Gas promotes the crystallization of nano-sized metal–organic frameworks in ionic liquid1. Issue 57 (21st July 2015) - Liu, Chengcheng; Zhang, Bingxing; Zhang, Jianling; Peng, Li; Kang, Xinchen; Han, Buxing; Wu, Tianbin; Sang, Xinxin; Ma, Xue
<x xml:space="preserve">Abstract</x> Gas can promote metal–organic framework (MOF) crystallization and MOF nanoparticles were obtained at room temperature.